Indonesia’s Decision to Cancel the Procurement of SU-35 from Russia 2019-2022 - Shadrina, Annisa; Riyanto, Sugeng (Proceedings of Universitas Muhammadiyah Yogyakarta Graduate Conference, 2023)
Indonesia’s well known as the archipelagic country with a lot of islands and a large territory to protect. Then, Indonesia must have an advanced defense system tool such as the fighter jet and decided to buy SU-35 from Russia by signed the MoU on February 14, 2018. Later, 2019, Indonesia decided to cancel the procurement of SU-35 from Russia. The goal of this study is to show the defense components of Indonesia which is consistent with Indonesia’s defense policy and how rational Indonesia’s decision making. This study uses a qualitive research method using an explanatory type of research in which it will reveal the problem raised through secondary data sources collected through journal articles, books, relevant internet pages, reports and documents that have credibility that can accounted for. The data analysis technique in this study uses content analysis, which is to analyze in-depth discussions of the content of written or printed information in various mass media. In line with rational model that explains how the decision making must rationally shows that the option to buy SU-35 from Russia has a lot of costs for Indonesia rather than the benefits related to Russia-Ukraine war that will make Indonesia in a wrong position in the world peace. The author proposes four rational reasons in Indonesia’s decision to cancel the procurement of SU-35 from Russia. Indonesia terkenal sebagai negara kepulauan dengan banyak pulau dan wilayah yang luas untuk dilindungi. Kemudian, Indonesia harus memiliki alat sistem pertahanan canggih seperti jet tempur dan memutuskan untuk membeli SU-35 dari Rusia dengan menandatangani MoU pada 14 Februari 2018. Kemudian pada tahun 2019, Indonesia memutuskan untuk membatalkan pengadaan SU-35 dari Rusia. Tujuan dari penelitian ini adalah untuk menunjukkan komponen pertahanan Indonesia yang sejalan dengan kebijakan pertahanan Indonesia dan seberapa rasional pengambilan keputusan Indonesia. Penelitian ini menggunakan metode penelitian kualitatif dengan jenis penelitian eksplanatori yang akan mengungkapkan permasalahan yang diangkat melalui sumber data sekunder yang dikumpulkan melalui artikel jurnal, buku, halaman internet yang relevan, laporan dan dokumen yang memiliki kredibilitas yang dapat dipertanggungjawabkan. Teknik analisis data dalam penelitian ini menggunakan analisis isi yaitu menganalisis pembahasan secara mendalam terhadap isi informasi tertulis atau cetak di berbagai media massa. Sejalan dengan model rasional yang menjelaskan bagaimana pengambilan keputusan harus rasional menunjukkan bahwa opsi untuk membeli SU-35 dari Rusia memiliki banyak biaya bagi Indonesia daripada keuntungan terkait perang Rusia-Ukraina yang akan membuat posisi Indonesia salah. perdamaian dunia. Penulis mengajukan empat alasan rasional dalam keputusan Indonesia membatalkan pengadaan SU-35 dari Rusia.